Comparaison du curriculum scolaire prescrit et des représentations des élèves. Le cas des positionnements entre savoirs scientifique et croyances religieuses en Grèce - Coralie Delhaye; Eleni Kalesi (Recherches en Éducation)
This study’s questions start from the observation of phenomena of rejection of scientific discourse in the name of religious discourse, or inverse phenomena, in education.The aim is to highlight the possible continuities or discontinuities between prescribed curriculum and students’ views in the case of a country where the school system is highly prescriptive and centralized. This study consists of a comparison between, on one hand, the positioning between science and religious beliefs officially prescribed in some programs, professor’s books and school textbooks, and on the other hand the positioning between science and religious beliefs really adopted by the students.The students position themselves strongly in favor of the autonomy between scientific knowledge and religious beliefs and, mildly, in disfavor of the fideist or classic concordist conceptions. This is only partially in line with the official curriculum. Indeed, although autonomy is part of the prescribed positioning and fideism of the proscribed positioning, complementarity does not seem to be part of the positions widely adopted and rationalist criticism is not rejected. Some explanations are put to the test and discussed in the text.